2018
DOI: 10.1016/j.bbalip.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PCSK9 levels and lipoprotein distribution are preserved in carriers of genetic HDL disorders

Abstract: Proprotein convertase subtilisin/kexin 9 (PCSK9), a protein regulating the number of cell-surface LDL receptors (LDLR), circulates partially associated to plasma lipoproteins. How this interaction alters PCSK9 plasma levels is still unclear. In the present study, we took advantage of the availability of a large cohort of carriers of genetic HDL disorders to evaluate how HDL defects affect plasma PCSK9 levels and its distribution among lipoproteins. Plasma PCSK9 concentrations were determined by ELISA in carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Interestingly, CSF samples extracted from AD patients have lower ex-vivo capacity to promote ABCA1-mediated cholesterol efflux compared to controls (Yassine et al, 2016). Finally, a further level of complexity could be the possible binding between PCSK9 and apoE-containing lipoproteins as previously described for LDL (Tavori et al, 2013), Lipoprotein (a) (Tavori et al, 2016) and HDL (Ferri et al, 2016a; Ruscica et al, 2018).…”
Section: Pcsk9 and Alzheimer’s Disease Pathogenesismentioning
confidence: 99%
“…Interestingly, CSF samples extracted from AD patients have lower ex-vivo capacity to promote ABCA1-mediated cholesterol efflux compared to controls (Yassine et al, 2016). Finally, a further level of complexity could be the possible binding between PCSK9 and apoE-containing lipoproteins as previously described for LDL (Tavori et al, 2013), Lipoprotein (a) (Tavori et al, 2016) and HDL (Ferri et al, 2016a; Ruscica et al, 2018).…”
Section: Pcsk9 and Alzheimer’s Disease Pathogenesismentioning
confidence: 99%
“…The minimum detectable PCSK9 concentration was 0.219 ng/mL. 23 Concerning the evaluation of PCSK9 in the conditioned medium, HepG2 cells were cultured in 12-well plates (6 Â 10 5 cells/well). The medium (200 mL) was collected after 24-hour treatment with leptin, resistin, and simvastatin.…”
Section: Elisa Assaysmentioning
confidence: 99%
“…However, since only 1 out of 175 Lp(a) particles binds to PCSK9, this would represent a very small percentage of total Lp(a) that is complexed [ 80 ]. Moreover, a study by our group showed that, irrespective of the presence of Lp(a), the analysis of PCSK9 lipoprotein distribution by Fast Protein Liquid Chromatography (FPLC) is not affected [ 81 ].…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 99%